Multi-year surveillance of selected avian pathogens in the migrant shorebird Red Knot (Calidris canutus rufa) at its main stopover site in Patagonia, Argentina - D'amico, Veronica Laura; González, Patricia M.; Baker, Allan J.; Buehler, Deborah M.; Bertellotti, Marcelo (Journal of Ornithology)
To investigate possible reasons for recent declines in Red Knot ( Calidris canutus rufa ) populations we surveyed for selected pathogens in Red Knots captured in San Antonio Bay, Argentina, on their northward migration during the period 2006–2011. Blood, cloacal swabs and faeces were analysed for bacteria [ Salmonella sp., Shigella sp., enteropathogenic Escherichia coli ( N = 42) and other coliforms ( N = 35)], viral agents [responsible for avian influenza ( N = 239), St. Louis encephalitis ( N = 51) and Newcastle disease ( N = 239)] and avian malaria parasites [ Plasmodium sp. and Haemo- proteus sp. ( N = 284)]. All 698 samples taken from 303 individuals were negative, providing no evidence that Red Knots sampled at this stopover site were infected with these pathogens at the time of sampling. Fil: D'amico, Veronica Laura. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico; Argentina Fil: González, Patricia M. Fundación Inalafquen; Argentina Fil: Baker, Allan J. Royal Ontario Museum; Canadá Fil: Buehler, Deborah M. University of Toronto; Canadá Fil: Bertellotti, Marcelo. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico; Argentina